Continuous periprosthetic bone loss but preserved stability for a collum femoris-preserving stem: follow-up of a prospective cohort study of 21 patients with dualenergy X-ray absorptiometry and radiostereometric analysis with minimum 8 years of follow-up - Nyström, Andreas; Kiritopoulos, Demostenis; Mallmin, Hans; Lazarinis, Stergios (Acta Orthopaedica, 2022)
Background and purpose — We previously described a decrease in bone mineral density (BMD) in the calcar region 2 years after insertion of the collum femoris-preserving (CFP) stem, but the implants were stable. Now we have examined the long-term changes in periprosthetic BMD and stability of the CFP stem. Patients and methods — We conducted a minimum 8-year follow-up of 21 patients from our original investigation. We examined periprosthetic BMD by dual-energy X-ray absorptiometry (DEXA) and implant stability by radiostereometric analysis (RSA). Results — Between 2 and 8 years 1 stem was revised due to aseptic loosening. Between 2 and 8 years we found a 14% (95% confidence interval [CI] 9–19) reduction in BMD in Gruen zone 6 and 17% (CI 6–28) in Gruen zone 7. From baseline the reduction in BMD was 30% (CI 23–36) in Gruen zone 6, 39% (CI 31–47) in Gruen zone 7, and 19% (CI 14–23) in Gruen zone 2. Between 2 and 8 years, RSA (n = 17) showed a mean translation along the stem axis of 0.02mm (CI –0.02 to 0.06) and a mean rotation around the stem axis of 0.08° (CI –0.26 to 0.41). From baseline mean subsidence was 0.07 mm (CI –0.16 to 0.03) and mean rotation around the stem axis was 0.23° (CI –0.23 to 0.68) at 8 years. Interpretation — There was continuous loss of proximomedial BMD at 8 years while the CFP stem remained stable. Proximal periprosthetic bone loss cannot be prevented by this stem.